(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This study aims to simplify programming learning for Arabic-speaking students of the Faculty of Information Technology by introducing a simple programming language in Arabic that covers the curriculum of the Programming 1 course. The proposed approach named ArPy (Arabic Python) is rule-based and enables the generation and execution of Python code from Arabic-written code through various steps, including preprocessing, lexical analysis, word mapping, and code generation. Additionally, it provides error detection during code execution. Experimental results have clearly validated that the implemented model (ArPy) is able to efficiently generate functional English Python code from Arabic code with a similarity accuracy of about 87%. Furthermore, ArPy has received positive feedbacks from the target users bridging the language barrier in the field of programming education in Arabic countries.